The role of the gatekeeper in formulating journalistic contents / journalists in the Kurdistan Region as a model A Field Research of the journalists in the Kurdistan Region as sample - Kazhal Muhammad Qader; Pave Jamel Ahmad (Zanco Journal of Humanity Sciences)
The researcher conducted a research entitled (The Role of the Gatekeeper in the Formulation of Journalistic Contents), the research problem is a set of main questions, the most important of which is (Does the Gatekeeper have a role in formulating journalistic contents in the press institutions?), The research objectives are a set of important goals derived from a problem The research, the most important of which is (knowledge of the role of the gatekeeper in formulating journalistic contents in press institutions), this research has a set of importance for journalists and academic education, the most important of which is (journalists' knowledge of a set of principles and laws that lead to the organization of journalistic work and also an increase in the percentage of sales Newspapers in the Kurdistan Region, all of this in order for the work of the journalist to be the fourth authority.